Local delivery of novel MRTF/SRF inhibitors prevents scar tissue formation in a preclinical model of fibrosis - Cynthia Yu-Wai-Man (Nature Portfolio, 2017)
Abstract The myocardin-related transcription factor/serum response factor (MRTF/SRF) pathway represents a promising therapeutic target to prevent fibrosis. We have tested the effects of new pharmacological inhibitors of MRTF/SRF signalling in a preclinical model of fibrosis. CCG-222740, a novel MRTF/SRF inhibitor, markedly decreased SRF reporter gene activity and showed a greater inhibitory effect on MRTF/SRF target genes than the previously described MRTF-A inhibitor CCG-203971. CCG-222740 was also five times more potent, with an IC50 of 5 μM, in a fibroblast-mediated collagen contraction assay, was less cytotoxic, and a more potent inhibitor of alpha-smooth muscle actin protein expression than CCG-203971. Local delivery of CCG-222740 and CCG-203971 in a validated and clinically relevant rabbit model of scar tissue formation after glaucoma filtration surgery increased the long-term success of the surgery by 67% (P < 0.0005) and 33% (P < 0.01), respectively, and significantly decreased fibrosis and scarring histologically. Unlike mitomycin-C, neither CCG-222740 nor CCG-203971 caused any detectable epithelial toxicity or systemic side effects with very low drug levels measured in the aqueous, vitreous, and serum. We conclude that inhibitors of MRTF/SRF-regulated gene transcription such as CCG-222740, potentially represent a new therapeutic strategy to prevent scar tissue formation in the eye and other tissues.